Komunikasi Interpersonal Yesus dan Implementasinya Bagi Pelayanan Gereja - Yolantya Widyasari (Institut Agama Kristen Negeri Palangka Raya, 2021)
Communication is certainly a primary aspect of church ministry. But the reality is that there are often imbalances that result in church divisions due to ineffective communication. The purpose of this paper is to find out how the communication that Jesus did, especially in interpersonal communication techniques and their implementation for church services. Interpersonal communication itself is defined as a state of interaction in face-to-face events. This study uses a literature study approach, namely by reading, taking notes and processing research materials. The description of this topic is from several stories of Jesus' interpersonal communication in the Gospels. The result of the theoretical study is how Jesus always paid attention to the communication component. He shapes the message by adjusting the various characteristics of the communicant and adapting to each context that occurs. Then Jesus is also able to overcome every disturbance well, and produces various extraordinary responses from each recipient of His message, and achieves the goal of effective interpersonal communication. The interpersonal communication that Jesus did can also be implemented in church services, namely pastoral counseling services. Komunikasi tentu menjadi aspek primer dalam pelayanan gereja. namun kenyataan yang dijumpai, seringkali terjadi ketimpangan yang mengakibatkan perpecahan gereja karena komunikasi yang tidak efektif. Tujuan penulisan ini mencoba menemukan bagaimana komunikasi yang Yesus lakukan, khususnya dalam teknik komunikasi interpersonal dan implementasinya bagi pelayanan gereja. Komunikasi interpersonal sendiri didefinisikan sebagai suatu keadaan interaksi dalam peristiwa tatap muka. Kajian ini menggunakan metode pendekatan studi pustaka, yaitu dengan membaca, mencatat dan mengolah bahan penelitian. Uraian topik ini, yaitu dari beberapa kisah komunikasi interpersonal Yesus dalam kitab-kitab Injil. Hasil kajian teori adalah bagaimana Yesus selalu memperhatikan komponen komunikasi. Ia membentuk pesan dengan menyesuaikan berbagai karakteristik komunikan dan menyesuaikan setiap konteks yang terjadi. Kemudian Yesus juga mampu mengatasi setiap gangguan dengan baik, dan menghasilkan berbagai respon yang luar biasa dari setiap penerima pesan-Nya, serta mencapai tujuan komunikasi interpersonal yang efektif. Komunikasi interpersonal yang Yesus lakukan juga dapat diimplementasikan dalam pelayanan gereja, yaitu salah satunya pelayanan pastoral konseling.